Deskripsi Nilai-Nilai Pendidikan Karakter dalam Pembelajaran Tematik Integral Sekolah Dasar Negeri 35 Pontianak Selatan - Vony Marsella; Kartono Kartono; Rio Pranata (Departement of Mathematics Education, 2024)
The purpose of this study was to describe character education values in lesson planning and describe character education values in thematic learning implementation in class IIIC of SD Negeri 35 South Pontianak. This research used descriptive qualitative method. The results of this study are to find out what character education values have been implemented in class IIIC of SD Negeri 35 South Pontianak. Researchers obtained the results by interviewing the IIIC class teacher in interviewing planning related to the value of character education, observation of the implementation in class IIIC was obtained by observing the IIIC class teacher at SDN South Pontianak.